Kepemimpinan Kepala Sekolah Efektif (Perspektif Pendidikan Islam) - Azhar, Sophia (el-Idarah: Jurnal Manajemen Pendidikan Islam, 2017)
In UUNo 20/2 003 (regulation number 2 0/2003) about national education system, it has been mentioned that national education is aimed to improve potentials of learner to be faithful person and to be democratic, responsible civilian. In the context of Islamic education It need to be run maximally by emphasizing religious value. Vision and mission need to determining and religious lesson is used as base in determining vision and mission of the institution. Use of principle of fastabiqul khairat becomes a value needed to create vision and mission determined, institution manager in must give an example to the staff by having good characteristic such as: sincere, honest, fair responsible, dynamic, practical and flexible. Effective and responsible head master is a person who can lead the education institution.